Monitoring matches and small-sided games in elite young soccer players - Darbellay, J.; Meylan, C. M. P.; Malatesta, D. (International Journal of Sports Medicine, 2020)
The aim of this study was to compare the distances at various intensity in matches and small-sided games in elite-young soccer players using the metabolic power approach and running speed methods through fixed and individual speed zones. The second aim was to investigate the difference in high intensity external workload (% of total distances covered > 16 km/h or > 20 W/kg) between matches and small-sided games. Global positioning system data from 14 elite-youth players were analyzed during 13 matches and two types of small sided-games. Five intensity zones were used to compare the running distances between the metabolic power approach and the classic performance analysis. Metabolic power recorded more distances covered at high intensity than the running speed methods for every playing situations, except for the zone 5 of fixed speed (> 19 km/h) in matches (P<0.05). Smaller differences of external workload at high intensity were found when using the metabolic power approach compared to the traditional performance analysis. Our results highlight that the traditional analysis underestimates the athlete`s high intensity efforts. The metabolic power approach seems more relevant to monitor matches and training situations but also to compare matches to small-sided games in elite-young soccer players.